2007
DOI: 10.3113/fai.2007.0295
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Subtalar Arthrodesis

Abstract: The results of isolated subtalar arthrodesis using a single screw for fixation are comparable to other fixation methods. Bone graft from local sites obviates the need for iliac crest autograft in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 15 publications
2
72
0
4
Order By: Relevance
“…Isolated subtalar arthrodesis is the preferred procedure in patients with clinical and radiographic arthritis confined to the subtalar joint that is refractory to conservative treatment [11,14,18,24]. Additive fusions of the talonavicular and calcaneocuboid joints, resulting in double [29] and triple arthrodeses [28,31], respectively, are done when arthritic joint changes, deformity and symptoms clearly extend to the midtarsal joints (Chopart's).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated subtalar arthrodesis is the preferred procedure in patients with clinical and radiographic arthritis confined to the subtalar joint that is refractory to conservative treatment [11,14,18,24]. Additive fusions of the talonavicular and calcaneocuboid joints, resulting in double [29] and triple arthrodeses [28,31], respectively, are done when arthritic joint changes, deformity and symptoms clearly extend to the midtarsal joints (Chopart's).…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of it are said to be an easier initial approach, availability of the denser talar bone and a reduced risk of damage to the neurovascular bundle [2,6,10].…”
Section: Discussionmentioning
confidence: 98%
“…During the last few decades internal fixation with screws has become established as the standard procedure for isolated subtalar arthrodesis [2,3,10]. In a biomechanical study, Chuckpaiwong et al [9] showed that a screw configuration (SC) using two arthrodesis screws instead of one could triple the initial compressive forces and also significantly increase rotatory stability of the arthrodesis construct [9].…”
Section: Introductionmentioning
confidence: 98%
“…Subtalar arthrodesis is an established treatment for severe hindfoot disorders when more conservative measures have failed, and fixation with large cannulated screws has become a standard method of achieving this (Davies et al, 2007;Easley et al, 2000). It is widely accepted that adequately rigid fixation and compression at the time of surgery are paramount for success of subtalar arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this surgery is solid fusion of the subtalar joint in a physiologically favorable position to eliminate painful motion. Internal fixation with screws is the method most commonly used to achieve fusion (Davies et al, 2007;Easley et al, 2000;Haskell et al, 2004;Mann et al, 1998), with attendant non-union rates ranging from 2% to 30% (Easley et al, 2000;Mann et al, 1998;Donley and Ward, 2002;Kolodziej and Nunley, 2001;Sammarco and Tablante, 1998). Union rate is negatively influenced by comorbidities such as tobacco use and diabetes, compromised bone at the arthrodesis site, and failed primary arthrodesis (Easley et al, 2000).…”
Section: Introductionmentioning
confidence: 97%